COMPETITIVENESS ANALYSIS OF INDONESIAN CINNAMON EXPORTS IN THE WORLD MARKET - Siswanto Imam Santoso; Lucky Sandya Pos Pos; Suryani Nurfadillah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Cinnamon is one of the leading plantation commodities that is most widely exported among other types of plantation products. Since the 1990s, Cinnamon has been in demand not only by the domestic market but also the world market so that it has become a potential plantation export commodity for Indonesia. This study aims to analyze the comparative and competitive advantages of Indonesian cinnamon exports in the world market, as well as the development and projection of Indonesian cinnamon exports in the world market. The study was conducted from January to March 2022. The research method uses a descriptive quantitative method with a Secondary Data Analysis (SDA) approach. The type of data used in this study is secondary data in the form of a time series in the form of data on Indonesian cinnamon exports to the world market for the period 2011 - 2020 which comes from various sources. The data analysis method uses exponential trend analysis to answer the development of Indonesian cinnamon exports and projections in the world market, the Revealed Comparative Advantages (RCA) analysis to analyze the comparative advantages of Indonesian cinnamon exports, as well as the Export Product Dynamic (EPD) method and the Trade Specialization Index (ITS) are used to determine the competitive advantage and performance of a commodity. The results showed that the competitiveness of Indonesian cinnamon exports for export destination countries of the United States, the Netherlands, Vietnam, Brazil, and Thailand had a strong competitiveness, indicated by the RCA value of 19.82. Export Product Dynamic (EPD) that often appears during the period 2011 - 2020 in the five export destination countries is rising star, then retreat, falling star, and the least appearing is lost oppurtinity. The results of the ITS analysis with a positive value of 0.92 show that Indonesia has a tendency to be a net exporter country. Cinnamon exports to the world market in 2011-2020 had an increasing trend every year and are projected to increase for 2021-2025.